Understanding and Treating Military Sexual Trauma - Zaleski, Kristen (Focus on Sexuality Research, 2018)
This authoritative update presents current findings on-and clinically and ethically sound responses to-the epidemic of sexual assault in the military. It examines in powerful detail how military culture enables a pervasive subculture of sexual violence, from consistently devaluing women to blaming victims and denying them justice. The author's dual attachment/trauma theory lens attends to a wide range of outcomes such as unit members closing ranks against survivors and the continuing impact of assault trauma on veterans' lives. And the book's second half critiques standard forms of treating military sexual trauma in favor of individualized therapy addressing the physical, psychological, and neurological aspects of trauma and recovery. This important volume covers: · Theory and history of sexual violence as a weapon of war. · Legal and health considerations in the aftermath of military sexual assault. · Critical distinctions between military and civilian legal response to sexual assault. · Variations in symptomology among survivors. · Specific barriers to services for male and LGBT survivors. · New and emerging treatment options for military sexual trauma/PTSD. This Second Edition of Understanding and Treating Military Sexual Trauma follows its predecessor as an essential reference on its subject for mental health clinicians treating sexual trauma in the military as well as trauma researchers, sociologists, women's health practitioners, and university students whose focus is women's studies, public policy, public health, social work, psychology, sociology, or political science. .